Dendriplex-Impregnated Hydrogels With Programmed Release Rate - Apartsin, Evgeny; Venyaminova, Alya; Majoral, Jean-Pierre; Caminade, Anne-Marie (Frontiers in Chemistry, 2022)
Hydrogels are biocompatible matrices for local delivery of nucleic acids, however, functional dopants are required to provide their efficient delivery into cells. In particular, dendrimers, known as robust nucleic acid carriers, can be used as such dopants. Herein, we report the first example of impregnating neutral hydrogels with siRNA-dendrimer complexes. The surface chemistry of dendrimers permits to adjust the release rate of siRNA-containing complexes. This methodology can bring new materials for biomedical applications.